Covid-19: Prevalence, Prevention, and Vaccination in Nintavur MOH Area, Sri Lanka - Riswan, Mohideenbawa (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Covid-19 is a global pandemic which affected almost 224 countries across the globe. Sri Lanka is also one of the countries which experienced the impacts of Coronavirus rampant on people, social system, education, livelihood, religious and cultural elements, and trade and finance of the country. Out of 354 MOH entities, Nintavur MOH area also struggles with Coronavirus pandemic from 2020 to till date. Almost 677 people were confirmed as infected cases and 17 people died due to this catastrophe. And altogether 2,518 persons from 991 families were victimized in terms of isolation or quarantine in the hospital, health care centers and homes. The health protocol and Covid-19 guidelines have strictly been adhered by Nintavur MOH, and monitored the prevalent situation, collecting samples for confirming infected cases, observing the quarantine persons and households, random testing of both PCR and RAT were carried out significantly in whole areas under its purview. And also the vaccination activities were undertaken by the Nintavur MOH to control the widespread of Covid-19. Yet, the study revealed that Health Staff from MOH have faced several difficulties in the initial stage of this Covid-19 epidemic and public support and awareness also were observed very poorly in the beginning. However, people are corporate and demanding vaccines and participation in the vaccination program in an effective manner in the new normal situation in the study area.